(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: This study analyzes sustainable coffee production and its competitive perspectives. The present study explains the understanding of sustainable production practices with a triple bottom line approach examining the relationship between production practices and competitiveness. The adoption of a sustainable development strategy has become important for companies as they cannot only be environment friendly but also gain a competitive advantage. The recent studies even found that environmental sustainability has a direct and positive relationship with competitiveness. Objective: The main objective of this study is to find out sustainable coffee production practices and competitive perspectives. Method: The research is descriptive. It explains the data and their characteristics statistically without manipulation. A structured questionnaire was used to collect the data using a survey method. Result: The most significant observation of the study is that the strenuous working condition of coffee production changes the living standard of the people in the community in the future. In this study, the majority of farmers responded that they were practicing sustainable coffee production. They were aware of the environmental aspect of coffee production practices and sustainable way of production leads to competitiveness in international markets. Conclusion: The research concluded that the independent variables economic aspect, social aspect, and environmental aspect of sustainable production practices have a significant positive relationship with competitiveness. Implication: The findings of the paper imply that the adoption of a sustainable development strategy has become more important for the companies as they cannot only be environment friendly but also gain a competitive advantage.